Look carefully at the argument below.
Let
|
a
|
=
|
b
|
Multiply both sides by a:
|
a2
|
=
|
ab
|
Add a2 - 2ab:
|
a2 + a2 -
2ab
|
=
|
ab + a2 - 2ab
|
Simplify:
|
2(a2 - ab)
|
=
|
a2 - ab
|
Divide by a2 - ab:
|
2
|
=
|
1
|
Oops!
What went wrong? It's the line which tells you to divide by a2 -
ab.
Since
a = b
you have divided by zero, and this leads to the final incorrect statement.
Since
a = b
you have divided by zero, and this leads to the final incorrect statement.
No comments:
Post a Comment
We would love to hear what you think about our post. Please post your comment here.